Significance of monoclonal antibodies against the conserved epitopes within non-structural protein 3 helicase of hepatitis C virus. - Yixin Bian; Shuoxian Zhao; Shaomei Zhu; Jinfeng Zeng; Tingting Li; Yongshui Fu; Yuanzhan Wang; Xin Zheng; Ling Zhang; Wenjing Wang; Baocheng Yang; Yuanping Zhou; et al. (PLoS ONE, 2013)
Nonstructural protein 3 (NS3) of hepatitis C virus (HCV), codes for protease and helicase carrying NTPase enzymatic activities, plays a crucial role in viral replication and an ideal target for diagnosis, antiviral therapy and vaccine development. In this study, monoclonal antibodies (mAbs) to NS3 helicase were characterized by epitope mapping and biological function test. A total of 29 monoclonal antibodies were produced to the truncated NS3 helicase of HCV-1b (T1b-rNS3, aa1192-1459). Six mAbs recognized 8/29 16mer peptides, which contributed to identify 5 linear and 1 discontinuous putative epitope sequences. Seven mAbs reacted with HCV-2a JFH-1 infected Huh-7.5.1 cells by immunofluorescent staining, of which 2E12 and 3E5 strongly bound to the exposed linear epitope (1231)PTGSGKSTK(1239) (EP05) or core motif (1373)IPFYGKAI(1380) (EP21), respectively. Five other mAbs recognized semi-conformational or conformational epitopes of HCV helicase. MAb 2E12 binds to epitope EP05 at the ATP binding site of motif I in domain 1, while mAb 3E5 reacts with epitope EP21 close to helicase nucleotide binding region of domain 2. Epitope EP05 is totally conserved and EP21 highly conserved across HCV genotypes. These two epitope peptides reacted strongly with 59-79% chronic and weakly with 30-58% resolved HCV infected blood donors, suggesting that these epitopes were dominant in HCV infection. MAb 2E12 inhibited 50% of unwinding activity of NS3 helicase in vitro. Novel monoclonal antibodies recognize highly conserved epitopes at crucial functional sites within NS3 helicase, which may become important antibodies for diagnosis and antiviral therapy in chronic HCV infection.